Biological characterization and in vitro fungicide screenings of a new causal agent of wheat Fusarium head blight in Tibet, China - Tang, Xiaoli; Yangjing, Gongsang; Zhuoma, Gusang; Guo, Xiaofang; Cao, Pengxi; Yi, Benlin; Wang, Wumei; Ji, De; Pasquali, Matias; Baccelli, Ivan; Migheli, Quirico; Chen, Xiaoyulong; et al. (Frontiers in Microbiology, 2022)
Wheat (Triticum aestivum L.) is an important cereal crop, widely grown throughout the temperate zones, and also suitable for cultivation at higher elevations. Fusarium head blight (FHB) is a highly destructive disease of wheat throughout the globe. In July 2020, serious wheat FHB symptoms were observed in open fields located in Linzhi City, southeast of Tibet, China. The causal agent was identified as Fusarium avenaceum (Fr.) Sacc. by amplification and sequencing of the internal transcribed spacer (ITS) region, translation elongation factor 1-alpha (EF-1α) gene, and RNA polymerase II subunit (RPB-2) gene, as well as by morphological characterization. Koch’s postulates were confirmed by a pathogenicity test on healthy spikes, including re-isolation and identification. To our knowledge, this is the first report of F. avenaceum causing FHB on wheat in Tibet, China. Moreover, to determine pathogen characteristics that may be useful for future disease management, the utilization of different carbon and nitrogen resources, temperature, light, and ultraviolet (UV) irradiation on mycelium growth and conidia germination were studied. Soluble starch and peptone were the best carbon, and nitrogen source for the pathogen respectively. The optimal temperatures for the pathogen’s mycelium growth and conidia germination were 15-20°C, matching the average temperature during the growing season in Linzhi (Tibet). Meanwhile, alternating 8-h light and16-h dark was shown to be conducive to mycelia growth, and complete darkness facilitated conidia germination. In addition, UV Irradiation of 48 MJ/cm2, approximately 100 times of the local condition, did not inhibit the germination of conidia. Furthermore, in vitro screening of effective fungicides was conducted. Among the seven tested pesticides, carbendazim showed the best inhibition rate, with an EC50 (concentration for 50% of maximal effect) value of 2.1 mg/L. Propiconazole also showed sufficient inhibitory effects against F. avenaceum, with an EC50 value of 2.6 mg/L. The study provides insights into the newly identified causal agent of wheat FHB in Tibet, China, as well as first pathogen characteristics and promising candidate substances for its management.